2017
DOI: 10.1038/nchembio.2489
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacology-based ceritinib repurposing using integrated functional proteomics

Abstract: Targeted drugs are effective when directly inhibiting strong disease drivers, but only a small fraction of diseases feature defined actionable drivers. Alternatively, network-based approaches can uncover new therapeutic opportunities. Applying an integrated phenotypic screening, chemical and phosphoproteomics strategy, we here describe the ALK inhibitor ceritinib to have activity across several ALK-negative lung cancer cell lines and identify new targets and network-wide signaling effects. Combining pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…To conclude, our strategy for identifying BRAF dimer kinase inhibitors demonstrates the significant value of screening specific phenotypic assays with additional kinase inhibitors to identify alternative uses and targets. There are several examples of kinase inhibitors that were developed for a specific kinase and indication, and later were found to have additional targets and effectiveness in a different cellular context or disease [51][52][53] . We foresee that a similar approach will be increasingly used to yield repurposing opportunities as well as chemical biology applications and drug development campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, our strategy for identifying BRAF dimer kinase inhibitors demonstrates the significant value of screening specific phenotypic assays with additional kinase inhibitors to identify alternative uses and targets. There are several examples of kinase inhibitors that were developed for a specific kinase and indication, and later were found to have additional targets and effectiveness in a different cellular context or disease [51][52][53] . We foresee that a similar approach will be increasingly used to yield repurposing opportunities as well as chemical biology applications and drug development campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…The specific design of drugs to intentionally target multiple kinases ("targeted polypharmacology") (193) is therefore likely to become a particularly important approach in the future of rational drug discovery. Phosphoproteomics has already begun to show promise here, through the repurposing of existing drugs after the discovery of off-target activities pointing to noncanonical but efficacious targets (194). In the future, the availability of phosphoproteomics data against every compound synthesized in drug discovery programs would enable the optimization of drugs against complex signaling network patterns, rather than attempting to maximize drug specificity against a single target.…”
Section: The Druggable Phosphoproteomementioning
confidence: 99%
“…The ATPindependent FAK inhibitors do not pass through the ATP binding site, but directly targets the FAK site, such as the FAK Y397 phosphorylation site [119]. Experimental results also showed that those small molecule FAK inhibitors could inhabit cell migration [3], survival [120], proliferation [121], and adhesion [122]. FAK inhibitors also can inhibit nuclear active FAK phosphorylation and regulate its related signaling pathways, such as the p53 signaling pathway, the inflammatory signaling pathway, the tumor angiogenesis-related pathway, and the immune escape signaling pathway.…”
Section: Fak Inhibitorsmentioning
confidence: 99%